1994
DOI: 10.1161/01.atv.14.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Response of plasma tissue factor pathway inhibitor to diet-induced hypercholesterolemia in crab-eating monkeys.

Abstract: Tissue factor pathway inhibitor (TFPI), a protease inhibitor associated with lipoproteins in plasma and endothelial cells, can inhibit the initial reactions of the tissue factor-mediated coagulation pathway. A positive relationship between TFPI and cholesterol has been demonstrated in human plasma. To investigate this relation in more detail, in the present study we measured TFPI in the plasma of monkeys on a high-cholesterol diet. After diet treatment, cholesterol levels and TFPI activity were increased 3-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The homology of the Kunitz‐type domains of TFPI among the three species is 57%, 86% and 69% in the first, second and third domains 57. The differences between rabbit and rat TFPI and those of human or monkey may be due to differences in the amino acid sequence, post‐transitional modification of TFPI, or species differences in the properties of the lipoproteins 60. The cDNA and predicted protein sequence for the full‐length mouse TFPI show significant homology to that of rat 61.…”
Section: Comparison Of Tfpi Across Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The homology of the Kunitz‐type domains of TFPI among the three species is 57%, 86% and 69% in the first, second and third domains 57. The differences between rabbit and rat TFPI and those of human or monkey may be due to differences in the amino acid sequence, post‐transitional modification of TFPI, or species differences in the properties of the lipoproteins 60. The cDNA and predicted protein sequence for the full‐length mouse TFPI show significant homology to that of rat 61.…”
Section: Comparison Of Tfpi Across Speciesmentioning
confidence: 99%
“…Cloning and expression of the mouse TFPI gene may offer useful information and material for coagulation studies performed in a mouse model system. However, in studying the regulatory roles of TFPI in thrombosis and atherosclerosis, species differences should be taken into consideration, especially if rabbits and rats are to be used as the animal model 60. Recently, a two‐Kunitz (Ixolaris) and a five‐Kunitz (Penthalaris) molecule with TFPI‐like properties have been described in the tick saliva from Ixodes scapularis 62, 63.…”
Section: Comparison Of Tfpi Across Speciesmentioning
confidence: 99%
“…The final concentration of TFPI under the present assay conditions ranged from 0.01 to 0.1 nM. It has been widely accepted that the C-terminus of TFPI is a major site for interactions of heparin, lipoproteins and phospholipids ; the significance of this region in anti-coagulant function has also been demonstrated [35,36]. Hansen et al [37] have reported that the lipoprotein-associated form of TFPI, which was estimated to account for 70-85 % of the circulating TFPI in human plasma, does not possess anti-coagulant function when the activity is determined in terms of diluted prothrombin time.…”
Section: Discussionmentioning
confidence: 88%
“…The principal role of TFPI appears to be to inhibit small amounts of TF, which are probably essential for the maintenance of normal haemostatic balance. A previous study has shown that TFPI in the plasma of crab-eating monkeys increases markedly in response to a high-cholesterol diet [52]. The effects of diets enriched with fats from various sources were explored by Larsen et al in a randomised crossover study that compared three dietary periods based on an olive oil-enriched diet, a sunflower oil diet and a rapeseed oil diet respectively [46].…”
Section: Tfmentioning
confidence: 99%